2002
DOI: 10.1128/mcb.22.20.7093-7104.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Stem-Loop Binding Protein Is Required for Efficient Translation of Histone mRNA In Vivo and In Vitro

Abstract: Metazoan replication-dependent histone mRNAs end in a conserved stem-loop rather than in the poly(A) tail found on all other mRNAs. The 3 end of histone mRNA binds a single class of proteins, the stem-loop binding proteins (SLBP). In Xenopus, there are two SLBPs: xSLBP1, the homologue of the mammalian SLBP, which is required for processing of histone pre-mRNA, and xSLBP2, which is expressed only during oogenesis and is bound to the stored histone mRNA in Xenopus oocytes. The stem-loop is required for efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
187
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 120 publications
(192 citation statements)
references
References 78 publications
5
187
0
Order By: Relevance
“…SLBP is required for the translation of stem-loop histone mRNAs (Sun et al, 1992;Gallie et al, 1996), and we have recently shown that SLBP stimulates translation of histone mRNA in vivo and in vitro (Sanchez and Marzluff, 2002). The SLBP that accumulates during maturation may play a role in activating translation of histone mRNA during oocyte maturation and after fertilization, thus providing the histone proteins necessary both for repackaging the sperm chromatin and for synthesis of histone proteins for the first S-phase.…”
Section: Discussionmentioning
confidence: 97%
“…SLBP is required for the translation of stem-loop histone mRNAs (Sun et al, 1992;Gallie et al, 1996), and we have recently shown that SLBP stimulates translation of histone mRNA in vivo and in vitro (Sanchez and Marzluff, 2002). The SLBP that accumulates during maturation may play a role in activating translation of histone mRNA during oocyte maturation and after fertilization, thus providing the histone proteins necessary both for repackaging the sperm chromatin and for synthesis of histone proteins for the first S-phase.…”
Section: Discussionmentioning
confidence: 97%
“…Under in vivo conditions, SLBP is likely to be an essential factor in processing of all histone pre-mRNAs regardless of the HDE sequence and the extent of base pairing to the U7 snRNA (Pandey et al, 1994). Following processing, SLBP remains associated with the stem-loop at the 3' end and accompanies the mature histone mRNA to the cytoplasm (Dominski et al, 1995;Erkmann et al, 2005;Whitfield et al, 2004), where it stimulates its translation into histone proteins (Gorgoni et al, 2005;Sanchez and Marzluff, 2002).…”
Section: Stem-loop Binding Protein (Slbp)mentioning
confidence: 99%
“…During 3' end processing the HDE interacts with the U7 snRNP and the stem-loop is recognized by a protein termed the stem-loop binding protein (SLBP) . After completion of processing, SLBP remains associated with the stem-loop at the end of mature histone mRNAs and stimulates their translation into histone proteins in the cytoplasm (Gorgoni et al, 2005;Sanchez and Marzluff, 2002). The intracellular concentration of SLBP reaches the highest level during S phase and rapidly declines during the S/G2 transition due to proteasome degradation (Whitfield et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This complex mediates histonespecific mRNA processing that results in mature mRNAs that do not contain a poly(A) tail but end in the stem-loop structure. The stem-loop and SLBP are also involved in translation of histone mRNAs (Gallie et al 1996;Ling et al 2002;Sanchez and Marzluff 2002). SLBP is associated with polyribosomes, dependent on the presence of intact histone mRNA (Whitfield et al 2004;S.…”
Section: Introductionmentioning
confidence: 99%